Security of South West Asia - Khalilzad, Zalmay (Aldershot, 1984)
Southwest Asia, stretching from Iran through Afghanistan to Pakistan and India, has become the focus of external superpower rivalry and the subject of great domestic and regional turmoil. These cross-cutting influences on the region are described and their effects analyzed in this book. The tribal, cultural, religious and political rivalries are complex, yet each in their way shape the security context and will determine the region's future. They are unlikely to be resolved and it is hard to imagine regional security arrangements capable of handling the tensions and potential for conflict. Outside powers, given the importance of the region, are likely to regard the region with concern and this will shape their policies towards it.
Keywords: East foreign relations